2011
DOI: 10.1590/s0044-59672011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Estudo fitoquímico biomonitorado pelos ensaios de toxicidade frente à Artemia salina e de atividade antiplasmódica do caule de aninga (Montrichardia linifera)

Abstract: ResumoMontrichardia linifera é uma planta aquática de amplo uso na medicina tradicional amazônica. entretanto, muito pouco se conhece sobre a sua composição química, e sua atividade biológica ainda não foi comprovada. na busca de substância(s) biologicamente ativa(s), este trabalho realizou um estudo fitoquímico biomonitorado no qual foram testados os extratos hexânico e etanólico obtidos do caule desta espécie, dos quais apenas o extrato etanólico foi selecionado para o fracionamento cromatográfico por ter ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
20

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 9 publications
0
26
0
20
Order By: Relevance
“…Esse é utilizado em ensaios biológicos por apresentar resultados rápidos, não exigir técnicas assépticas e ser de baixo custo, podendo ser encontrado facilmente no comércio. [14][15][16] Proposto por Michael e colaboradores, 17 o bioensaio é amplamente utilizado correlacionando estudos em microcrustáceos com atividade biológicas, tais como toxinas fitoquímicas, [18][19][20] …”
Section: Introductionunclassified
“…Esse é utilizado em ensaios biológicos por apresentar resultados rápidos, não exigir técnicas assépticas e ser de baixo custo, podendo ser encontrado facilmente no comércio. [14][15][16] Proposto por Michael e colaboradores, 17 o bioensaio é amplamente utilizado correlacionando estudos em microcrustáceos com atividade biológicas, tais como toxinas fitoquímicas, [18][19][20] …”
Section: Introductionunclassified
“…The toxicity results of the BHESC and LHESP extracts are also valuable, since samples that are toxic to A. salina can contain bioactive compounds with antitumor, antimalarial, trypanosomicidal, and insecticidal potential [38], possible antiplasmodic activity [39], and antimicrobial effect [40]. …”
Section: Resultsmentioning
confidence: 99%
“…This fact is measured by the great number of published researches in which was used this method. Examples of LC 50 determined using A. salina, reporting studies of some plant extracts include: Montrichardia linifera (60.4 µg mL -1 ), 12 Plectranthus neochilus Schltr (210.3 µg mL -1 ), 13 Lychnophora trichocarpha (672.4 µg mL -1 ), 14 Bromelia antiacantha Bertol (362.1 µg mL -1 ), 15 Sonchus oleraceus (5,120.0 µg mL -1 ), 16 Pithecellobium cochliocarpum (257.5 µg mL -1 ) 17 and Mimosa caesalpiniifolia Benth (1,765.0 µg mL -1 ). 18 To evaluate the lethality conducted on A. salina it is necessary to correlate the concentration of the species extract in a saltwater medium with the quantity of micrustacean nauplii dead.…”
mentioning
confidence: 99%
“…Different methodologies cite the use of DMSO surfactant to aid in achieving better solubility of ethanol extracts. 12,14,16,[19][20][21] In our experience with lethality tests conducted on A. salina with essential oils, it was found that the use of Tween 80 as a surfactant was appropriate for the species of Piper: P. cernuum Vell., P. glabratum Kunth., P. hispidum Sw., and P. aff. Madeiranum.…”
mentioning
confidence: 99%